Tourism Cooperation between China and Thailand: Opportunities, Challenges, and the influences on Sustainable Tourism Development - Hou, Shuyu (Prince of Songkla University, 2023)
Master of Business Administration (Hospitality and Tourism Management (International Program)), 2023